Microbiological evaluation of frozen fruit pulp sold at public fairs in Macapá, Amapá (Research, Society and Development, 2020)
The fruit pulp preserves several nutritional characteristics of the fruits and for this reason they are highly appreciated. However, due to the difficulties in sanitary inspection, little is known about the hygienic-sanitary conditions of its processing, which can pose health risks if good hygienic practices are not followed during the pulp manufacturing process. In this way, the present research had the objective of analyzing the microbiological characteristics of pulps (pineapple, mango and passion fruit) marketed in the popular fairs of the Buritizal and Jardim Felicidade neighborhoods in the city of Macapá-AP. 500g to 1kg of fruit pulp (pineapple, mango and passion fruit) were collected at fairs in two districts of the city of Macapá-AP, after which they were submitted to microbiological analysis for thermotolerant coliforms and Salmonella ssp at the IEPA Laboratory. It was observed that in all the samples studied were negative for Salmonella ssp, however, three samples were positive for thermotolerant coliforms and were outside the parameters required by the legislation. It was possible to verify that fruit pulp producers still need to improve sanitary and sanitary issues and to provide higher quality food safety for these products consumed by the population.